(untitled) (Педагогіка вищої та середньої школи, 2003)
The article is devoted to problem o f reflection a basic science in school subject. Characteristics o f biological science and school knowledge and cognition are distinguished. The ties between them are established. The question about there dynamic is considered fo r biological courses in 7-9 forms.